Flow and heat transfer characteristics in channels with piriform dimples and protrusions (2023)
The flow and heat transfer behaviour of channels with dimples and protrusions of spherical and piriform shapes was numerically explored by solving the Navier-Stokes and energy equations with a CFD software, the ANSYS Fluent 19.3, in the range of Reynolds numbers from 8,500 to 59,000. The values of the Nusselt number and friction factors were estimated and the non-dimensional Performance Evaluation Criterion (PEC) was determined to measure the thermal-hydraulic performance. The results reveal that the piriform protruded channel demonstrated a higher thermal performance with Nusselt number values of 36%, 15%, 23%, and 9% than the smooth, spherical dimpled, piriform dimpled, and spherical protruded channels, respectively. This indicates that heat transfer is enhanced by the turbulent mixing caused by the roughened surfaces of the channels. Nevertheless, the smooth channel had the lowest pressure drop with the friction factor of 20%, 7%, 21% and 27% less than that of spherical dimpled, piriform dimpled, spherical protruded, and piriform protruded channels, respectively. In the Reynolds number range, lower Nusselt number ratios and friction factor ratios were observed in the piriform dimpled channel compared to other enhanced-surface channels. The overall performance based on the thermal-hydraulic analysis indicated that the channel with piriform protrusions performed better with the highest PEC value of 3.77 times higher than the smooth-surface channel.